(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The present study aims to evaluate the level of parental emotional responsiveness as perceived by kindergarten children in Latakia city, Syria, and to determine the significance of differences in perceived parental emotional responsiveness in terms of the “child’s gender” and “child’s age” variables. In order to achieve the research goals, a random sample of kindergarten children was selected, with a sample size of 103 children in the age range of 4 to 5 years. The researcher applied the descriptive method and prepared a child-directed pictorial scale, taking into account the relevant cognitive features of children during this developmental stage. The study found an intermediate level of perceived responsiveness, and furthermore determined the existence of a statistically significant difference in said perception in terms of the “child’s gender” variable, and no statistically significant difference in terms of the “child’s age” variable.